#TITLE_ALTERNATIVE# - RANU INTAN (NIM 12206044); Pembimbing: Dr.Ir. Pudjo Sukarno, PUTI
Tight gas reservoir is a reservoir which has a large amount of reserves and relatively easy to be produced compared with non-conventional gas reservoirs others, though not a high production potential. Thus the need to drill holes made possible increased production potential, such as by implementing multilateral drilling technology. Relative multilateral wells have a greater production capacity than vertical wells, though it cost more than vertical drilling. Therefore, for tight gas reservoirs will be applied to one of modern drilling technology that can help produce gas from tight reservoirs of drilling multilateral wells. The method to optimize production considering two factors, namely in terms of technique as well as consideration of its economic aspect. Optimization is performed starting from the reservoir modeling, and then create a multilateral wells to produce a plateau rate for 60 years. In addition, the objectives of utilizing gas from tight gas reservoirs for domestic electricity needs. In connection with efforts to increase the productivity of wells are needed economic study by considering the sensitivity of parameters such as number and length of the lateral holes of multilateral well and the sensitivity of economic variables. In case of developing tight gas reservoirs, selected two kinds of scenarios. The first scenario is to sell gas to industrial production output in need, while the second scenario is the production process the gas to be converted into electric power to fulfill the electricity needs of households. From these two scenarios, will be seen how the benefits and the factors that influence the amount of such benefits. Sensitivity of the economic variables are made to the variation in gas prices, MARR, and the cost of electricity per month per housing unit